Potassium Phthalimide (PPI): An Efficient and Green Organocatalyst for the One-pot Synthesis of 6-amino-1,4-dihydropyrano[2,3-c]-pyrazole-5- carbonitrile Derivatives under Microwave Irradiation - H. Vekariya, Rajesh; D. Patel, Kinjal; P. Prajapati, Neelam; D. Patel, Hitesh (Current Microwave Chemistry, 2017)
Background: Potassium phthalimide (PPI), a mild, green and commercially available organocatalyst used in the synthesis of a wide range of important bioactive compounds. 6-amino-1,4- dihydropyrano[2,3-c]-pyrazole-5-carbonitrile derivatives were synthesized via a four component reaction of ethyl acetoacetate, hydrazine hydrate, aryl aldehydes and malononitrile by utilizing various homogenous as well as heterogeneous catalysts, which usually involve relatively lower product yields and prolonged reaction times. We describe a simple and straightforward protocol to prepare pyrano[2,3-c]-pyrazole derivatives that address these drawbacks. Methods: Utilizing microwave irradiation (MWI) and with the use of water as a universal and green solvent, a series of 6-amino-1,4-dihydropyrano[2,3-c]-pyrazole-5-carbonitrile derivatives (5a-5o) have been efficiently prepared from the four component reaction of ethyl acetoacetate, hydrazine hydrate, aryl aldehydes and malononitrile. Results: The reactions proceeded in short periods of time (3-4 min) without side products, affording the products in 91-97 % yields. Reactions under microwave conditions were faster than those achieved with conventional heating. Water showed better result compared to other organic solvents in terms of product yield and reaction time. Conclusion: Short reaction times, mild reaction conditions, excellent product yields, use of inexpensive catalyst and easy work-up procedure and no use of toxic organic solvents are remarkable advantages of this approach. The discussed methodology can be applied to generate a variety of 6-amino- 1,4-dihydropyrano[2,3-c]-pyrazole-5-carbonitrile derivatives, which serve as precursors to compounds of pharmaceutical interest.
Keywords: Pyrano[2